Cardioprotection of Electroacupuncture for Enhanced Recovery after Surgery on Patients Undergoing Heart Valve Replacement with Cardiopulmonary Bypass: A Randomized Control Clinical Trial. (16th February 2017) - Zhang, Fangxiang; Yu, Xiangdi; Xiao, Hong
Abstract : We attempted to investigate cardioprotection of electroacupuncture (EA) for enhanced recovery after surgery on patients undergoing heart valve replacement with cardiopulmonary bypass. Forty-four patients with acquired heart valve replacement were randomly allocated to the EA group or the control group. Patients in the EA group received EA stimulus at bilateral Neiguan (PC6), Ximen (PC4), Shenting (GV24), and Baihui (GV20) acupoints twenty minutes before anesthesia induction to the end of surgery. The primary end point was cardioprotection effect of electroacupuncture postoperatively and the secondary endpoints were quality of recovery and cognitive functioning postoperatively. The present study demonstrated that electroacupuncture reduced the occurrence of complications and played a role of cardioprotective effect on patients after heart valve replacement surgery with cardiopulmonary bypass, and it benefits patients more comfortable and contributes to recovery after surgery. This trial is registered with ChiCTR-IOC-16009123 .